Multi-screen marketing : the seven thing you need to know to reach your customers across TVs, computers, tablets and mobile phones - Hritzuk, Natasha; Jones, Kelly (Hoboken : Wiley & Sons, Inc., 2014)
'Advertising is being transformed by the move from traditional TV spots and static advertising placements to'multi-screen' marketing, where consumers control their own flow of content through smartphones, tv's, tablets, and pc's. This is an unprecedented opportunity for marketers. This book explains why the secret to effective multi-screen marketing is NOT to focus on devices (tablets, mobile phones, and computers) but on the ways customers use them, in order to deliver the right screen with the right message in the right moment. Effective multi-screen marketing brings more relevance to consumers, and more value for marketers.The authors identify four main types of multi-screen customer behavior: Content Grazing, which occurs when consumers use two or more screens simultaneously to access separate or unrelated content. Quantum Leaping, which occurs when consumers start an activity on one screen and continue it on another. Investigative Spider-Webbing, where consumers view related content on two or more devices at the same time. Social Spider-Webbing, the mirror image of Investigative Spider-Webbing that is extroverted and focused on sharing and connecting. In addition to new research and data on how customers behave in a multi-screen world, the book includes real-world examples from marketers and companies who are embracing a consumer-centric approach to multi-screen marketing, and evoke ways companies can use technology in service to people, rather than the other way around'--
Includes bibliographical references (pages 241-243) and index.
Keywords: Internet marketing; Electronic commerce